Analisis Fatwa Dr. Syauqi Ibrahim ‘Allam Tentang Eksploitasi Ilegal Tanah Negara - Al Wafa, Mohammad Hassan; Hakim, Nur (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2025)
The dense population and growing economic needs are leading humanity toward a new way of life. One of the fundamental needs of every person is the need for a place to live and reside. The exploitation of state-owned land, whether in cities or the wilderness, has become inevitable. State land, which should be managed by the government and used for the welfare of society, is often seized and used for personal interests. Dr. Syauqi Ibrahim Allam, a grand mufti at the Egyptian fatwa institution, stated in his book Fiqh al-Wathan wa al-Muwathonah that using state land without permission is forbidden (haram) and is considered gasab (unlawful usurpation). He also urged those involved in such acts to vacate and return the land to its rightful authority. How did he determine the legal basis for his fatwa? What are the implications for Indonesia? This article reviews Dr. Syauqi Ibrahim Allam's perspective on the illegal use of state land, a practice now common in Indonesia, as a moral and ethical compass. To analyze this, the author employs descriptive analysis within the framework of qualitative research methodology.The findings indicate that Dr. Syauqi Ibrahim Allam's fatwa is well-grounded in religious texts and is also supported by the views of Ahlus Sunnah scholars from the four major schools (madhabs), with a particular alignment to the Hanafi school, which strictly requires permission from the leader (imam) for the use of state land. He equates the illegal use of state land to the gasab of private properties. This fatwa is crucial for public understanding, given the numerous issues arising from land disputes with the government.